STRIKING INSIDE ANGOLA WITH 32 BATTALION - Sebalane, Thato (Scientia Militaria - South African Journal of Military Studies, 2014)
The Angolan Bush War or the South African Border War has become something of a forgotten war. In South Africa, the war was heard of, but the details were not known to the general public. For all practical purposes it was a ‘secret war’. “Relatives and friends had no idea what their loved ones were going through while serving [on] the border” (p 13). Today many South Africans have a limited or eschewed understanding of why there was a border war or, for that matter, explain why South Africa was entangled in a quagmire of that sort for years on end in Angola. The consistent stream of border war literature has tried to fill this void; the main contributors from South Africa were at first commanding officers (veteran colonels and retired generals) but thereafter numerous former conscripts. The declassification of information paved a way for aspiring researchers interested uncovering this ‘secret war’. More recently, the opposing sides have started to chronicle “their side of the story” and record details of “their” experiences. A recent contribution is Gennady Shubin and Andrei Tokarev’s Bush War: the road to Cuito Cuanavale. Soviet Soldiers’ Accounts of the Angolan War. 2011. Auckland Park: Jacana Media (Pty) Ltd.